2016
DOI: 10.1111/faf.12170
|View full text |Cite
|
Sign up to set email alerts
|

Claiming seafood is ‘sustainable’ risks limiting improvements

Abstract: Over the past decade, the sustainability of seafood production has improved and is cause for ocean optimism. In an attempt for recognition of ongoing efforts, many producers and food retailers now claim products are ‘sustainable’. What exactly does this mean and could we limit further improvement using this claim? Here, we discuss the sustainable/sustainability dichotomy, and the problem of communicating continual improvement in terms of grand and absolute claims – that is ‘We sell 100% sustainable product.’ W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Concern has been raised that certification can only drive improvement so far because once a fishery or farm is certified, there is no impetus for further improvement, which therefore makes sustainability a static rather than dynamic goal (Bush, Toonen, Oosterveer, & Mol, 2013;Tlusty, 2012;Tlusty & Thorsen, 2016). The lack of improvement also occurs because of over-promising to deliver a sustainable product.…”
Section: Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern has been raised that certification can only drive improvement so far because once a fishery or farm is certified, there is no impetus for further improvement, which therefore makes sustainability a static rather than dynamic goal (Bush, Toonen, Oosterveer, & Mol, 2013;Tlusty, 2012;Tlusty & Thorsen, 2016). The lack of improvement also occurs because of over-promising to deliver a sustainable product.…”
Section: Certificationmentioning
confidence: 99%
“…This ceases further improvement because why (or how) do they improve when the product is sustainable? The mere transition to discussing "sustainability" instead of "sustainable" can promulgate continuous improvement (Tlusty & Thorsen, 2016;Tlusty et al, 2012).…”
Section: Certificationmentioning
confidence: 99%
“…In addition, market-based approaches such as ecolabels and third-party certification (e.g., MSC and Aquaculture Stewardship Council) also work to influence the middle of the chain. These efforts have been critiqued for varied weaknesses concerning the nature of standards, implementation, and unintended consequences, [13][14][15][16][17] but still certification remains a major focus in the seafood industry. Tlusty and others showed that most certification approaches in aquaculture were essentially similar in their strategies and goals and therefore are wide open for innovation.…”
Section: Specifying Sectors Of Supply Chains and The Global Productiomentioning
confidence: 99%
“…The scope of a developmental standard could reflect the need to support the capabilities of producers or communities of producers to continually improve their production rather than setting a single and 'fictitious' level or goal of sustainability (Micheli et al, 2014;Tlusty & Thorsen, 2016). In practical terms, such a standard could follow Ivarsson and Alvstam (2010) and focus on new process-oriented categories, such as the provision of technological and organizational assistance, co-innovation, human capacity building, and/or financial and administrative advice.…”
Section: New or Existing Certification Schemes?mentioning
confidence: 99%